Criteria for the evaluation of innovativeness of independent film production company in the perspective of creativity - Vitkauskaitė, Ieva (Creativity Studies, 2023)
This study aims to identify the criteria for evaluating the innovativeness of an independent film production company in the European film market. Innovativeness of a company consists of inputs to innovation and outputs from innovation. It reveals a company’s potential to implement innovations, which are often sources of competitive advantage. The empirical study involved 29 experts from the European film industry and film production companies. Experts were asked to evaluate 60 criteria in total. The survey results suggest that a company’s innovativeness can currently be evaluated by 51 criteria, of which 15 are the most important. The criteria identified for evaluating a company’s innovativeness are ranked in order of importance for determining a company’s innovativeness. The results obtained allow us to evaluate the innovativeness of a company by comparing independent film production companies with one another in the European film market and thus to determine which company is more innovative. It also makes possible new hypotheses to be raised, analysed and tested. It should be noted that the article was written based on a dissertation in progress.